A 1.0GPa-level coating-free hot stamping steel and a preparation method thereof
By adjusting the content and combination of alloy elements, the problems of 1.0GPa-grade hot stamped steel are solved, and the problems of easy oxidation and insufficient hydrogen resistance at high temperatures are achieved, and the high strength, oxidation and hydrogen-induced delayed cracking resistance are achieved. It is suitable for Car body safety structural parts.
Patent Information
- Application Number
- CN202411323396.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing 1.0GPa grade hot stamped steel is prone to oxidation at high temperatures, and has insufficient anti-hydrogen-induced delayed cracking performance, making it difficult to have high strength, oxidation and hydrogen resistance.
By adjusting the addition and content of alloy elements, Al+Si+Cr+RE elements are introduced to ensure that there is no oxidation of iron sheets during hot stamping of the sheet, and by regulating the Mn, B, Cr, and Mo content, it forms a total martensite or Martensite or Martensite by regulating the content of Mn, B, Cr, and Mo. Body + less than 35% bainite structure, and microalloy carbides are formed as hydrogen traps such as Nb, V, Ti, Mo.
It has achieved high strength, high-temperature oxidation resistance and hydrogen-induced delayed cracking resistance of 1.0GPa grade hot stamping steel, and replaced the coating hot-formed steel and is suitable for automotive body safety structural parts.
Smart Images

Figure CN118854169B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hot stamping steel, and in particular to a 1.0 GPa-level coating-free hot stamping steel and a preparation method thereof. Background Art
[0002] With the rapid development of the automotive industry, the requirements for lightweight vehicles are becoming increasingly higher. Ultra-high strength and toughness automotive steel is one of the most economical and effective solutions for lightweight vehicles, and is of great significance in alleviating the dual carbon reduction pressure from the manufacturing and application ends. However, as the strength of steel increases, its room temperature formability decreases, limiting the application of high-strength steel.
[0003] Hot stamping technology uses a process of high-temperature forming followed by quenching and hardening, which can perfectly solve the contradiction between strength and formability. In order to ensure collision safety, automotive components need to have sufficient resistance to collision invasion and rely on good deformation ability to absorb the energy brought by the collision. Although most existing hot-formed steels have ultra-high strength, the bending fracture strain value, an important parameter representing their collision safety, is relatively low. How to increase the fracture strain of hot-formed steel to ensure the energy absorption effect has become one of the key scientific and technological difficulties.
[0004] For 1.0GPa grade hot stamping steel, delayed cracking resistance is also important. If the fracture strain of the material is high, its delayed cracking resistance is also high. In addition, conventional uncoated hot stamping sheets are usually 2 The sheet is heated to above 900 ℃ in a heating furnace with protective gas for austenitization. However, it is inevitable to expose the sheet to the air during the process of transferring it from the heating furnace to the mold and forming it. The surface is severely oxidized. The iron oxide scale that falls off in the mold needs to be cleaned in time during the production process, which seriously reduces the production efficiency. The formed parts also need to be shot peened or sand blasted to remove the oxide layer, resulting in reduced part dimensional accuracy and increased part cost due to the increase in processes. At present, Al-Si plating and Zn plating technologies are commonly used to avoid the generation of iron oxide scale, but the quality control of the plating is difficult, the processes are complicated, the manufacturing cost is also high, and there is a patent blockade. If the hot stamping steel material can be made anti-oxidized at high temperatures through innovation in material composition and process, it can replace the plating product.
[0005] A Chinese patent with publication number CN110643909A discloses an anti-oxidation ultra-high strength steel plate for hot stamping and a low-temperature hot forming process thereof. The alloy composition contains 6% to 8% Mn and 2% to 5% Cr. The prices of Mn and Cr elements are relatively high, so the alloy cost is relatively high. In addition, a high Mn content is not conducive to welding performance.
[0006] The Chinese patent with publication number CN117265225A discloses a coating-free hot-formed steel and a preparation method thereof, comprising the following raw materials in mass percentage: C: 0.3%~0.45%, Si: 0.8%~1.5%, Mn: 1.2%~2.5%, Cr: 0.8%~2.4%, Ti: 0.01%~0.02%, B: ≤0.002%, Ni: 0.05%~0.15%, Mo: ≤0.3%, Nb: 0.04~0.1%, Al: 0.05~0.20%, P, S: ≤0.02%, and the rest are Fe and unavoidable impurity elements. It can be seen from the composition of this steel that it contains high C and Mn contents, which will inevitably lead to poor weldability, bending fracture strain and other indicators, and its resistance to hydrogen-induced delayed cracking is correspondingly poor.
[0007] The Chinese patent with publication number CN114130842A involves a method for removing oxide scale from high Cr-Si alloyed 1000~1800MPa grade hot-formed steel, which provides an oxide scale removal process combining hydrochloric acid pickling and EPS treatment; the C content in the 1000MPa grade hot-formed steel alloy composition involved in the patent is 0.15~0.35%, which determines that the invented steel type cannot have a very high bending fracture strain, and its resistance to hydrogen-induced delayed cracking is poor.
[0008] Therefore, it is of great significance to provide a 1.0 GPa grade hot stamping steel that has high strength, high temperature oxidation resistance and resistance to hydrogen-induced delayed cracking. Summary of the invention
[0009] The technical problem solved by the present invention is to provide a 1.0 GPa-level coating-free hot stamping steel having high strength, high temperature oxidation resistance and hydrogen-induced delayed cracking resistance.
[0010] In view of this, the present application provides a 1.0 GPa-grade uncoated hot stamping steel, which comprises, by mass percentage: C 0.06~0.10%, Mn 0.8~1.1%, Si 0.8~1.5%, Al 0.10~0.30%, Ti 0.015~0.030%, Cr 1.9~3.0%, (La+Ce) 0.005~0.05%, B 0.0005~0.0025%, (Nb+V+Mo) 0.03~0.26%, 2.7%≤Si+Cr≤4.0%, Ti / N≥3.5, and Fe balance.
[0011] Preferably, the content of Mn is 0.9-1.0%, and the content of B is 0.0019-0.0022%.
[0012] Preferably, the Cr content is 2.0-2.8%, 3.0%≤Si+Cr≤3.8%, and 1.1%≤Al+Si≤1.7%.
[0013] Preferably, the content of (Nb+V+Mo) is 0.05-0.24%.
[0014] Preferably, the content of (La+Ce) is 0.008-0.03%.
[0015] Preferably, the N content is ≤0.005%.
[0016] The present application also provides a method for preparing the hot stamping steel, comprising the following steps:
[0017] S1) mixing the raw materials according to the composition ratio, smelting the obtained mixed raw materials, and then continuously casting to obtain a slab; during the smelting process, a magnesium-based alloy is used for deoxidation, and the magnesium-based alloy includes 55-63wt% Mg, 19-22wt% Al, 10-18wt% Ca, and 2.5-3.5wt% Ba;
[0018] S2) sequentially heating, dephosphorizing, rough rolling, finish rolling, laminar cooling and coiling the slab to obtain a hot rolled coil;
[0019] S3) removing the iron oxide scale from the hot rolled coil, heating the obtained sheet to 890-950° C., and then transferring the sheet to a die for hot stamping and quenching.
[0020] Preferably, the P content in the smelted molten steel is ≤0.010%; the magnesium-based alloy is added in the form of iron cored wire, the timing of adding is 30 to 35 seconds after the smelted molten steel is tapped, and the amount of the iron cored wire added is 3.0 to 4.0 kg / t.
[0021] Preferably, the final rolling temperature of the finishing rolling is 850-900°C, and the final rolling thickness is 1.4-2.5 mm; the laminar cooling adopts the front-stage cooling method, the upper header cooling rate is 49-58%, the lower header cooling rate is 75-80%, and the coiling temperature is 550-620°C;
[0022] The method for removing the iron oxide scale adopts one or both of pickling treatment and EPS production line treatment; the acid solution of the pickling is one or both of hydrochloric acid and hydrofluoric acid, and the pickling is carried out in acid tank 1, acid tank 2 and acid tank 3 in sequence, the acid solution concentration of the acid tank 1 is 60-80g / L, the acid solution concentration of the acid tank 2 is 85-110g / L, and the acid solution concentration of the acid tank 3 is 115-145g / L. The temperature of the pickling is 85-95°C and the speed is 85-150m / min.
[0023] Preferably, in step S3), the heating time = (sheet thickness × 125 + 60~100) s, the transfer time is 3~10 s, the heating atmosphere is dry compressed air, dry nitrogen or dry argon, and the dew point is -30~-5°C; the hot stamping pressure is 1~20 MPa, the holding time is 3~15 s, and the quenching is to 80~180°C.
[0024] The present application provides a 1.0 GPa-level coating-free hot stamping steel, which comprises, by mass percentage, C 0.06~0.10%, Mn 0.8~1.1%, Si 0.8~1.5%, Al 0.10~0.30%, Ti 0.015~0.030%, Cr 1.9~3.0%, (La+Ce) 0.005~0.05%, B 0.0005~0.0025%, (Nb+V+Mo) 0.03~0.26%, 2.7%≤Si+Cr≤4.0%, N≤0.005%, Ti / N≥3.5, and Fe balance. The hot stamping steel provided in the present application introduces Al+Si+Cr+RE (La+Ce) elements and accurately controls the proportion of the elements, so that no iron oxide scale is produced during hot stamping of the sheet; the content of Mn, B, Cr, and Mo is controlled to ensure that the 1.0GPa-level hot stamping steel has good hardenability, so that its structure after hot stamping and quenching is a full martensite structure or a martensite + less than 35% bainite structure; the use of elements such as Nb, V, Ti, and Mo is conducive to the formation of microalloy carbides as hydrogen traps, and the martensitic phase transformation point Ms temperature can also be controlled, so that when the 1.0GPa-level hot stamping steel is quenched, sufficient ε or η carbides are obtained as hydrogen traps; therefore, the hot stamping steel provided in the present application has high strength, high temperature oxidation resistance, and hydrogen-induced delayed cracking resistance by adding the above-mentioned alloy elements and adjusting the content.
[0025] Furthermore, in the preparation process of hot stamping steel, the present application introduces magnesium-based alloy deoxidation during the smelting process, strictly limits the P content to less than 0.010%, reduces P segregation at the grain boundaries, and further improves the hot stamping steel's resistance to hydrogen-induced delayed cracking.
[0026] The experimental results show that the quenched state of the hot stamping steel prepared in this application has: tensile strength of 1100~1250MPa, yield strength of 800~980MPa; the maximum bending angle corresponding to the maximum load of VDA238-100 three-point bending of the quenched sheet is ≥96° (1.8mm sheet), and the four-point bending hydrogen embrittlement test of the quenched sheet does not break for more than 550h in HCl with pH=1. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1A secondary electron image of the hot stamping steel structure prepared in Example 1 of the present invention;
[0028] Figure 2 The engineering stress-strain curve diagram of the hot stamping steel prepared in Example 1 of the present invention;
[0029] Figure 3 This is a VDA238-100 three-point bending angle-bending stress curve of the hot stamping steel prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0031] In view of the performance requirements of hot stamping steel in the prior art, the present application provides a 1.0 GPa-level coating-free hot stamping steel, which ensures its resistance to hydrogen-induced delayed cracking by adjusting the addition and content of alloy elements and utilizing composite micro-alloyed carbides and transition carbides. At the same time, based on "Al+Si+Cr+RE", no iron oxide scale is generated during hot stamping of sheet materials, and can replace coated hot stamping steel for use in automobile body safety structural parts. Specifically, an embodiment of the present invention discloses a 1.0 GPa-level coating-free hot stamping steel, which includes, by mass percentage, C 0.06~0.10%, Mn 0.8~1.1%, Si0.8~1.5%, Al 0.10~0.30%, Ti 0.015~0.030%, Cr 1.9~3.0%, (La+Ce) 0.005~0.05%, B0.0005~0.0025%, (Nb+V+Mo) 0.03~0.26%, 2.7%≤Si+Cr≤4.0%, N≤0.005%, Ti / N≥3.5, and Fe balance.
[0032] In the 1.0 GPa-level coating-free hot stamping steel provided in the present application, the C content is 0.06-0.10%, specifically, the C content is 0.07-0.09%; for example, the C content in the present application is 0.06%, 0.07%, 0.08%, 0.09% or 0.10%.
[0033] The content of Mn is 0.8-1.1%. Specifically, the content of Mn is 0.8%, 0.9%, 1.0% or 1.1%.
[0034] The Ti content is 0.015-0.030%, specifically, the Ti content is 0.018-0.028%; for example, the Ti content in the present application is 0.016%, 0.017%, 0.018%, 0.019%, 0.020%, 0.021%, 0.022%, 0.023%, 0.024%, 0.025%, 0.026%, 0.027%, 0.028%, 0.029% or 0.030%.
[0035] La and Ce, as rare earth elements, can deeply reduce the harmful effects of low melting point elements such as S and P. At the same time, trace amounts of rare earth elements can also improve the high temperature oxidation resistance of the material. However, if too much La+Ce is added, the nozzle will be blocked during the continuous casting process. The content of La+Ce is 0.005~0.05%, specifically, the content of La+Ce is 0.008~0.03%, and more specifically, the content of La+Ce is 0.01~0.02%.
[0036] The Si content is 0.8-1.5%, specifically, the Si content is 0.9-1.2%; for example, the Si content in this application is 1.0%, 1.1%, 1.3%, and 1.4%.
[0037] The Cr content is 1.9-3.0%, specifically, the Cr content is 2.0-2.8%; for example, the Cr content in the present application is 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7% or 2.9%.
[0038] On the basis of limiting the respective contents of Si and Cr, the present application further limits the total amount of the two added in the hot stamping steel to better ensure oxidation resistance while also preventing excessive costs and difficulty in removing oxide scale; 2.7%≤Si+Cr≤4.0%, further, 3.0%≤Si+Cr≤3.8%, and further, 3.2%≤Si+Cr≤3.4%.
[0039] The content of Al is 0.10-0.30%. For example, the content of Al is 0.10%, 0.12%, 0.15%, 0.20%, 0.25% or 0.28%.
[0040] The content of B is 0.0005-0.0025%, specifically, the content of B is 0.0008-0.0024%, more specifically, the content of B is 0.0019-0.0022%; for example, the content of B in the present application is 0.0006%, 0.0007%, 0.0009, 0.0010%, 0.0011%, 0.0012%, 0.0013%, 0.0014%, 0.0015%, 0.0016%, 0.0017%, 0.0018%, 0.0020%, 0.0021% or 0.0023%.
[0041] In the present application, one or more of Nb, V and Mo are added, that is, Nb, V and Mo can be added in one of the three, two of the three, or all three at the same time; the total addition amount of (Nb+V+Mo) is 0.03-0.26%, specifically, the total addition amount of (Nb+V+Mo) is 0.05-0.24%, more specifically, the total addition amount of (Nb+V+Mo) is 0.11-0.22%; for example, the total addition amount of (Nb+V+Mo) is 0.04%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.23%, 0.25%. In a specific embodiment, Nb is added alone, or Nb and V are added, or Mo is added alone.
[0042] N may be introduced into hot stamping steel, specifically N≤0.005%. Further, Ti / N≥3.5 is limited to fix N with Ti to ensure the effectiveness of solid solution B; more specifically, Ti / N is 4.3, 6.0, and 9.0.
[0043] Furthermore, the present application also provides a method for preparing hot stamping steel, comprising the following steps:
[0044] S1) mixing the raw materials according to the composition ratio, smelting the obtained mixed raw materials, and then continuously casting to obtain a slab; during the smelting process, a magnesium-based alloy is used for deoxidation, and the magnesium-based alloy includes 55-63wt% Mg, 19-22wt% Al, 10-18wt% Ca, and 2.5-3.5wt% Ba;
[0045] S2) heating, dephosphorizing, rough rolling, finish rolling, laminar cooling and coiling the slab to obtain a hot rolled coil;
[0046] S3) removing the iron oxide scale from the hot rolled coil, heating the obtained sheet to 890-950° C., and then transferring the sheet to a die for hot stamping and quenching.
[0047] In the preparation process of hot stamping steel, the present application first prepares the ingredients according to the composition ratio, melts the obtained mixed raw materials, and then continuously casts them to obtain slabs; during the smelting process, a low-Ca + low-Al magnesium-based composite deoxidizing alloy is used for steelmaking deoxidation to avoid the formation of clustered / strip-shaped alumina after steelmaking Al deoxidation, thereby improving the quality of molten steel and avoiding the problem of easy blockage of water outlets. The composition of the deoxidized alloy is specifically composed of the following components: 58-61wt% Mg, 20-21.2wt% Al, 13-16wt% Ca, 2.8-3.2wt% Ba; it is first prepared into alloy particles of 70-100mm, and then made into iron cored wire (the skin is iron, and the core is a magnesium-based composite deoxidized alloy) through a cored operation, and the cored wire is added to the molten steel through a wire feeder after the steel tapping is completed; 3.0-4.0kg / t of iron cored wire is added when the molten steel is tapped 30-35s; more specifically, the particle size of the alloy particles is 80-90mm, and 3.5-3.8kg / t of iron cored wire is added when the molten steel is tapped 32-34s. The molten steel obtained by smelting is then used to prepare slabs through a continuous casting device, and the continuous casting device is well known to those skilled in the art, and this application does not impose any special restrictions on this.
[0048] The present application then sequentially heats, dephosphorizes, roughs, finishes, laminarly cools and coils the slab to obtain a hot-rolled coil; each of the above steps is performed in accordance with technical means well known to those skilled in the art; it should be noted that the dephosphorization process is strictly controlled during the roughing and finishing stages. The final rolling temperature of the finishing rolling is 850-900°C, and the final rolling thickness is 1.4-2.5mm. Specifically, the final rolling temperature of the finishing rolling is 860°C, 870°C, 880°C, and 890°C, and the final rolling thickness is 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2.0mm, 2.1mm, 2.2mm, 2.3mm, and 2.4mm; the laminar cooling adopts a front-stage cooling method, and the upper header cooling The cooling rate is 49~58%, and the cooling rate of the lower header is 75~80%. Specifically, the cooling rate of the upper header is 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, and the cooling rate of the lower header is 76%, 77%, 78%, 79%; the coiling temperature is 550~620℃, specifically, the coiling temperature is 560℃, 570℃, 580℃, 590℃, 600℃, and 610℃.
[0049] According to the present invention, after the hot-rolled coil is obtained, the oxide scale on its surface is removed, specifically, one or both of pickling treatment and EPS production line treatment are used to remove the oxide scale; the pickling acid solution is one or both of hydrochloric acid and hydrofluoric acid, and the pickling is carried out in acid tank 1, acid tank 2 and acid tank 3 in sequence, the acid concentration of acid tank 1 is 60-80g / L, the acid concentration of acid tank 2 is 85-110g / L, and the acid concentration of acid tank 3 is 115-145g / L; specifically, the acid concentration of acid tank 1 is 65-75g / L, the acid concentration of acid tank 2 is 90-105g / L, and the acid concentration of acid tank 3 is 150-160g / L. 3 has an acid concentration of 125-140 g / L; the pickling temperature is 85-95 ° C, and the speed is 85-150 m / min. Specifically, the pickling temperature is 86-90 ° C, and the speed is 100-120 m / min; during the pickling process, the acid concentration of the acid tank is increased successively, and different degrees of damage to the oxide layer can be achieved. Among them, the outermost oxide layer is easy to pickle, and a lower concentration of acid is used, and then the acid concentration is increased successively to better remove the iron oxide layer from the outside to the inside. In this way, the efficiency of removing the iron oxide scale is better and more effective, and the disadvantage of unclean pickling of local areas of hot-rolled coils in a single acid tank can be avoided. The EPS production line treatment can use recycled harmless medium water and steel sand to remove the surface oxide scale and achieve rust prevention. In the process of removing the oxide scale in this application, pickling treatment is first used and then EPS production line treatment is used.
[0050] In the present application, the pickled slab is finally hot stamped; the hot stamping is specifically as follows: the sheet after the oxide scale is removed is heated to austenitization (890-935°C) and kept warm for a certain time, the total heating time = (material thickness × 125 + 60-100) s, and then quickly transferred to the mold for quenching to 80-180°C within 3-10 seconds, the pressure is 1-20 MPa, and the holding time is 3-15 seconds (determined according to the thickness of the sheet); the above heating is carried out in a box furnace, a roller hearth furnace or an induction furnace, and the atmosphere of the furnace during heating can be dry compressed air or other gases such as N 2 , Ar dry gas, the dew point is controlled at -30~-5°C. In the above process, the heating temperature is specifically 900~925°C, the heating time is specifically 300~380s, the pressure is 10~18MPa, and the pressure is maintained for 7~12s; the quenching temperature is 100~150°C.
[0051] The present invention provides a 1.0GPa-level coating-free, hydrogen-induced delayed cracking resistant hot stamping steel and a preparation method thereof, which utilizes composite microalloyed carbides and transition carbides to ensure its hydrogen-induced delayed cracking resistance, and at the same time, based on "Al+Si+Cr+RE (La+Ce)", achieves the generation of no iron oxide scale during hot stamping of sheet metal, and can replace coated hot stamping steel for use in automobile body safety structural parts, with a relatively broad market prospect. The experimental results show that the quenched state of the 1.0GPa-level coating-free, hydrogen-induced delayed cracking resistant hot stamping steel provided by the present application: tensile strength 1100~1250MPa, yield strength 800~980MPa; the maximum bending angle corresponding to the maximum load of the quenched sheet metal in the VDA238-100 three-point bending ≥96° (1.8mm sheet metal), and the four-point bending hydrogen embrittlement test of the quenched sheet metal does not break for more than 550h in HCl with pH=1.
[0052] In order to further understand the present invention, the 1.0 GPa-level coating-free hot stamping steel provided by the present invention is described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0053] The detection methods of different performances in the following embodiments are specifically as follows:
[0054] VDA238-100 bending angle test: The energy absorption of automotive safety components is closely related to the bending performance of materials. Well-known automobile companies such as BMW and Mercedes-Benz usually use the VDA 238-100 three-point bending test standard formulated by the German Association of the Automotive Industry to evaluate the energy absorption effect of parts; the sample size is 60×60 mm 2 Before testing, the decarburized layer or oxide layer on the surface of the sample was ground off. The support shaft diameter was 30 mm, the bending punch radius was 0.4 mm, the preload was set to 30 N before the experiment, the punch moving speed was 10 mm / min, and the test was stopped when the force dropped by 60 N after the downward bending reached the maximum force value.
[0055] Thickness of decarburized layer after hot stamping: Use an optical microscope or scanning microscope to observe the sample interface. The ferrite area at the edge is the decarburized layer area. Use IPP software or the tool that comes with the microscope to measure the thickness.
[0056] Four-point bending hydrogen embrittlement fracture time: a rectangular specimen of 15×115mm is obtained from the steel plate, and the length direction of the specimen is perpendicular to the rolling direction of the steel plate; a typical specimen is selected for tensile property test on a tensile testing machine to obtain the yield strength of the material in the hot stamping quenching state; the specimen is prestressed by a four-point bending fixture. For hot stamping steel, it is difficult for the material to deform or slightly deform under service conditions. Therefore, the prestress σ is generally selected as a percentage of the yield strength, and the maximum does not exceed 1.1 times the yield strength; the loaded specimen is immersed in a solution, which is a 0.1mol / L (pH=1) hydrochloric acid solution; during the immersion process, the pH value is tested and adjusted every 24 hours to ensure that the pH value is always 1±0.2. There are 3 to 5 parallel specimens in each group of stress levels. If one cracked specimen appears, it is determined to be cracked. The stress level of this patent is selected as 100% yield strength.
[0057] The present invention provides 3 embodiments and 2 comparative examples, and the alloy compositions are specifically shown in Table 1;
[0058] Table 1 Chemical composition data of hot stamping steel provided in Examples and Comparative Examples (wt%)
[0059]
[0060] Example 1
[0061] The preparation of 1.0GPa-level coating-free, hydrogen-induced delayed cracking-resistant hot stamping steel specifically includes the following steps:
[0062] Step S1: preparing ingredients according to the weight percentage of each element in the composition data table of Table 1, with the remainder being Fe and unavoidable impurities, smelting the prepared raw materials, and using a low-Ca, low-Al magnesium-based composite deoxidizing alloy for steelmaking and deoxidation during the smelting process. The chemical composition mass percentage of the deoxidizing alloy is specifically 58% Mg, 21.2% Al, 18% Ca, and 2.8% Ba. The deoxidizing alloy is first prepared into alloy particles with a particle size of about 80 mm. When the molten steel is tapped for 32 seconds, a cored wire of 3.5 kg / t Fe is added into the molten steel, and the molten steel is deoxidized and inclusions are modified. After that, each component is smelted and continuously cast into a slab;
[0063] Step S2: The slab is subjected to heating, descaling, rough rolling, finishing rolling, laminar cooling and coiling to obtain a hot rolled coil; wherein, the descaling process is strictly controlled in the rough rolling and finishing rolling stages, the final rolling temperature in the finishing rolling stage is 880°C, and the final thickness of the finishing rolling is 1.8mm; the laminar cooling adopts the front-stage cooling method, the upper and lower header cooling rates are: 58% and 78%, and the coiling temperature is 580°C;
[0064] Step S3: using hydrochloric acid as the acid solution, the acid solution concentration of acid tank 1 is 65g / L, the acid solution concentration of acid tank 2 is 85g / L, and the acid solution concentration of acid tank 3 is 125g / L; adjusting the pickling temperature to 95°C, and then pickling the hot-rolled coil at a pickling speed of 100m / min; after pickling, using recycled harmless medium water and steel grit in the EPS production line to remove surface oxide scale and achieve rust prevention;
[0065] Step S4: Cut the pickled coil into blanks in the shape of parts, place the blanks in a heating furnace and heat them to 925°C to austenitize them and keep them warm for 300s. The dew point in the furnace is -20°C and the atmosphere is N 2 , and then quickly transferred to the die for hot stamping and quenching. The transfer time was 7s. The pressure of the hot stamped part in the rapid press was 10MPa. After holding the pressure for 10s, the die was quenched to 100°C. The sheet after hot stamping was prepared into a metallographic sample, and no decarburized layer was found.
[0066] The hot-formed steel prepared in step S4 is prepared into a sample of 60×60 mm, and the bending angle under the maximum load is determined to be 100° by a three-point bending test according to the VDA238-100 standard.
[0067] The quenched specimens were prepared into four-point bending specimens of 15×115 mm. The specimens were bent and fixed on a four-point bending device at a yield deflection of 100%. They were then placed in hydrochloric acid with a pH of 1 and did not break for 600 hours.
[0068] Figure 1 is the secondary electron image of the hot stamping steel structure after quenching in this embodiment. Figure 1 It can be seen that the metallographic structure of the hot stamping steel after quenching is full martensite.
[0069] Figure 2 is the engineering stress-strain curve of the hot stamping steel after quenching in this embodiment, Figure 2 It can be seen that the yield strength is 970MPa, the tensile strength is 1145MPa, and the total elongation is 6.3%.
[0070] Figure 3 is a three-point bending angle-bending stress curve of VDA238-100 hot stamping steel after quenching in this embodiment, Figure 3 It can be seen that the VDA bending angle corresponding to the maximum bending load is 100°.
[0071] Example 2
[0072] The preparation of 1.0GPa-level coating-free, hydrogen-induced delayed cracking-resistant hot stamping steel specifically includes the following steps:
[0073] Step S1: preparing ingredients according to the weight percentage of each element in the composition data table of Table 1, with the remainder being Fe and unavoidable impurities, smelting the prepared raw materials, and using a low-Ca, low-Al magnesium-based composite deoxidizing alloy for steelmaking and deoxidation during the smelting process. The chemical composition mass percentage of the deoxidizing alloy is specifically 58% Mg, 21.2% Al, 18% Ca, and 2.8% Ba. The deoxidizing alloy is first prepared into alloy particles with a particle size of about 80 mm. When the molten steel is tapped for 32 seconds, a cored wire of 3.5 kg / t Fe is added into the molten steel, and the molten steel is deoxidized and inclusions are modified. After that, each component is smelted and continuously cast into a slab;
[0074] Step S2: The slab is subjected to heating, descaling, rough rolling, finishing rolling, laminar cooling and coiling to obtain a hot rolled coil; wherein, the descaling process is strictly controlled in the rough rolling and finishing rolling stages, the final rolling temperature of the finishing rolling is 860°C, and the final thickness of the finishing rolling is 2.5mm; the laminar cooling adopts the front-stage cooling method, the cooling rates of the upper and lower headers are 58% and 80%, and the coiling temperature is 620°C;
[0075] Step S3: using hydrochloric acid as the acid solution, the acid solution concentration of acid tank 1 is 60g / L, the acid solution concentration of acid tank 2 is 85g / L, and the acid solution concentration of acid tank 3 is 145g / L; adjusting the pickling temperature to 85°C, and then using a pickling speed of 150m / min to pickle the hot-rolled coil; after pickling, using recycled harmless medium water and steel grit in the EPS production line to remove surface oxide scale and achieve rust prevention;
[0076] Step S4: Cut the pickled coil into blanks in the shape of parts, heat the blanks to 925°C to austenitize them and keep them warm for 380 seconds. The atmosphere is dry compressed air and the dew point in the furnace is -30°C. Then quickly transfer them to the mold for hot stamping and quenching. The transfer time is 10 seconds. The pressure of the hot stamped parts in the rapid press is 20 MPa. After the holding time is 15 seconds, the mold is quenched to 180°C. Take the hot stamped sheet to prepare a metallographic sample, and no decarburized layer is found.
[0077] The hot-formed steel prepared in step S4 was prepared into a sample of 60×60 mm. The bending angle under the maximum load was determined to be 97° by a three-point bending test according to VDA238-100 standard.
[0078] The quenched specimens were prepared into four-point bending specimens of 15×115 mm. The specimens were bent and fixed on a four-point bending device at a yield deflection of 100%. They were then placed in hydrochloric acid with a pH of 1 and did not break for 600 hours.
[0079] Example 3
[0080] The preparation of 1.0GPa-level coating-free, hydrogen-induced delayed cracking-resistant hot stamping steel specifically includes the following steps:
[0081] Step S1: preparing ingredients according to the weight percentage of each element in the composition data table of Table 1, with the remainder being Fe and unavoidable impurities, smelting the prepared raw materials, and using a low-Ca, low-Al magnesium-based composite deoxidizing alloy for steelmaking and deoxidation during the smelting process. The chemical composition mass percentage of the deoxidizing alloy is specifically 58% Mg, 21.2% Al, 18% Ca, and 2.8% Ba. The deoxidizing alloy is first prepared into alloy particles with a particle size of about 80 mm. When the molten steel is tapped for 32 seconds, a cored wire of 3.5 kg / t Fe is added into the molten steel, and the molten steel is deoxidized and inclusions are modified. After that, each component is smelted and continuously cast into a slab;
[0082] Step S2: The slab is subjected to heating, descaling, rough rolling, finishing rolling, laminar cooling and coiling to obtain a hot rolled coil; wherein, the descaling process is strictly controlled in the rough rolling and finishing rolling stages, the final rolling temperature of the finishing rolling is 900°C, and the final thickness of the finishing rolling is 1.4mm; the laminar cooling adopts the front-stage cooling method, the cooling rates of the upper and lower headers are: 49% and 75%, and the coiling temperature is 560°C;
[0083] Step S3: using hydrochloric acid + hydrofluoric acid (volume ratio of 5:1) as the acid solution, the hydrochloric acid concentration of acid tank 1 is 80 g / L, the acid concentration of acid tank 2 is 110 g / L, and the acid concentration of acid tank 3 is 125 g / L; adjusting the pickling temperature to 90°C, and then pickling the hot-rolled coil at a pickling speed of 120 m / min; after pickling, using recycled harmless medium water and steel grit in the EPS production line to remove surface oxide scale and achieve rust prevention;
[0084] Step S4: Cut the pickled coil into blanks in the shape of parts, and then hot stamp, heat the part blank to 925°C to austenitize it and keep it warm for 300s, the atmosphere is dry compressed air, the dew point in the furnace is -5°C, and then quickly transfer it to the mold for hot stamping and quenching, the transfer time is 3s, the pressure of the hot stamped part in the fast press is 1MPa, and the mold is quenched to 80°C after the holding time of 3s; take the hot stamped sheet to prepare a metallographic sample, and no decarburized layer is found;
[0085] The hot-formed steel prepared in step S4 is prepared into a sample of 60×60 mm. The bending angle under the maximum load is determined to be 109° by a three-point bending test according to VDA238-100 standard.
[0086] The quenched specimens were prepared into four-point bending specimens of 15×115 mm. The specimens were bent and fixed on a four-point bending device at a yield deflection of 100%. They were then placed in hydrochloric acid with a pH of 1 and did not break for 600 hours.
[0087] Comparative Example 1
[0088] The preparation of 1.0GPa-level coating-free, hydrogen-induced delayed cracking-resistant hot stamping steel specifically includes the following steps:
[0089] Step S1: mixing ingredients according to the weight percentage of each element in the composition data table of Table 1, with the remainder being Fe and unavoidable impurities, smelting the mixed raw materials, and then continuously casting them into slabs;
[0090] Step S2: The slab is subjected to heating, descaling, rough rolling, finishing rolling, laminar cooling and coiling to obtain a hot rolled coil; wherein, the descaling process is strictly controlled in the rough rolling and finishing rolling stages, the final rolling temperature of the finishing rolling is 880°C, and the final thickness of the finishing rolling is 1.8mm; the laminar cooling adopts the front-stage cooling method, the cooling rates of the upper and lower headers are 50% and 70%, and the coiling temperature is 600°C;
[0091] Step S3: using hydrochloric acid as the acid solution, adjusting the pickling temperature to 92° C., and then pickling the hot rolled coil at a pickling speed of 100 m / min; after pickling, recycling harmless medium water and steel grit in the EPS production line to remove surface oxide scale and achieve rust prevention;
[0092] Step S4: Cut the pickled coil into blanks in the shape of parts, heat the blanks to 925°C to austenitize them and keep them warm for 300s, the atmosphere is dry compressed air, the dew point in the furnace is -15°C, and then quickly transfer them to the mold for hot stamping and quenching. The transfer time is 7s, the pressure of the hot stamping parts in the fast press is 10MPa, and the mold is quenched to 80°C after the holding time of 10s; take the hot stamped sheet to prepare a metallographic sample, and the decarburized layer thickness is 2μm;
[0093] The hot-formed steel prepared in step S4 is prepared into a sample of 60×60 mm. The bending angle under the maximum load is determined to be 89° by a three-point bending test according to VDA238-100 standard.
[0094] The quenched specimens were prepared into four-point bending specimens of 15×115 mm. The specimens were bent on a four-point bending device at a yield deflection of 100% and fixed. They were then placed in hydrochloric acid with a pH of 1. The time for cracks to appear on the surface of the specimens was 303 h.
[0095] Comparative Example 2
[0096] The preparation of 1.0GPa-level coating-free, hydrogen-induced delayed cracking-resistant hot stamping steel specifically includes the following steps:
[0097] Step S1: mixing ingredients according to the weight percentage of each element in the composition data table of Table 1, with the remainder being Fe and unavoidable impurities, melting the mixed raw materials, and then continuously casting them into slabs;
[0098] Step S2: The slab is subjected to heating, descaling, rough rolling, finishing rolling, laminar cooling and coiling to obtain a hot rolled coil; wherein, the descaling process is strictly controlled in the rough rolling and finishing rolling stages, the final rolling temperature of the finishing rolling is 900°C, and the final thickness of the finishing rolling is 2.5mm; the laminar cooling adopts the front-stage cooling method, the cooling rates of the upper and lower headers are 58% and 78%, and the coiling temperature is 600°C;
[0099] Step S3: using hydrochloric acid as the acid solution, adjusting the pickling temperature to 93°C, and then pickling the hot rolled coil at a pickling speed of 100 m / min; after pickling, recycling harmless medium water and steel grit in the EPS production line to remove surface oxide scale and achieve rust prevention;
[0100] Step S4: Cut the pickled coil into blanks in the shape of parts, heat the blanks to 925°C to austenitize them and keep them warm for 380 seconds. The atmosphere is dry compressed air and the dew point in the furnace is -15°C. Then quickly transfer them to the mold for hot stamping and quenching. The transfer time is 8 seconds. The pressure of the hot stamped parts in the rapid press is 20MPa. After the holding time is 15 seconds, the mold is quenched to 180°C. Take the hot stamped sheet to prepare a metallographic sample, and the decarburized layer thickness is 3μm.
[0101] The hot-formed steel prepared in step S4 is prepared into a sample of 60×60 mm. The bending angle under the maximum load is determined to be 90° by a three-point bending test according to VDA238-100 standard.
[0102] The quenched specimens were prepared into four-point bending specimens of 15×115 mm. The specimens were bent on a four-point bending device at a yield deflection of 100% and fixed. They were then placed in hydrochloric acid with a pH of 1. The time for cracks to appear on the surface of the specimens was 486 h.
[0103] The mechanical properties, oxide layer thickness and four-point bending hydrogen embrittlement fracture time of the hot stamping steel prepared in the embodiment and the comparative example are shown in Table 2 below:
[0104] Table 2 Mechanical properties of hot stamping steel after quenching in the examples and comparative examples
[0105]
[0106] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0107] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A 1.0 GPa-grade coating-free hot stamping steel, comprising, by mass percentage: C0.06~0.10%, Mn 0.8~1.1%, Si 0.8~1.5%, Al 0.10~0.30%, Ti 0.015~0.030%, Cr 1.9~3.0%, N content ≤0.005%, (La+Ce) 0.005~0.05%, B 0.0005~0.0025%, (Nb+V+Mo) 0.03~0.26%, 2.7%≤Si+Cr≤4.0%, Ti / N≥3.5, Fe balance; The microstructure after hot stamping and quenching is full martensite or martensite + less than 35% bainite.
2. The hot stamping steel according to claim 1, characterized in that: The content of Mn is 0.9 to 1.0%, and the content of B is 0.0019 to 0.0022%.
3. The hot stamping steel according to claim 1, characterized in that: The Cr content is 2.0-2.8%, 3.0%≤Si+Cr≤3.8%, 1.1%≤Al+Si≤1.7%.
4. The hot stamping steel according to claim 1, characterized in that: The content of (Nb+V+Mo) is 0.05-0.24%.
5. The hot stamping steel according to claim 1, characterized in that: The content of (La+Ce) is 0.008-0.03%.
6. The method for preparing the hot stamping steel according to claim 1, comprising the following steps: S1) preparing the raw materials according to the composition ratio, smelting the obtained mixed raw materials, and then continuously casting to obtain a slab; during the smelting process, a magnesium-based alloy is used for deoxidation, and the magnesium-based alloy includes 55-63wt% Mg, 19-22wt% Al, 10-18wt% Ca, and 2.5-3.5wt% Ba; S2) sequentially heating, dephosphorizing, rough rolling, finish rolling, laminar cooling and coiling the slab to obtain a hot rolled coil; S3) removing the iron oxide scale from the hot rolled coil, heating the obtained sheet to 890-950° C., and then transferring it to a die for hot stamping and quenching.
7. The preparation method according to claim 6, characterized in that: The P content in the smelted molten steel is ≤0.010%; the magnesium-based alloy is added in the form of iron cored wire, the addition timing is 30 to 35 seconds after the smelted molten steel is tapped, and the addition amount of the iron cored wire is 3.0 to 4.0 kg / t.
8. The preparation method according to claim 6, characterized in that: The final rolling temperature of the finishing rolling is 850-900°C, and the final rolling thickness is 1.4-2.5mm; the laminar cooling adopts the front-stage cooling method, the upper header cooling rate is 49-58%, the lower header cooling rate is 75-80%, and the coiling temperature is 550-620°C; The method for removing the iron oxide scale adopts one or both of pickling treatment and EPS production line treatment; the acid solution of the pickling is one or both of hydrochloric acid and hydrofluoric acid, and the pickling is carried out in acid tank 1, acid tank 2 and acid tank 3 in sequence. The acid concentration of acid tank 1 is 60-80g / L, the acid concentration of acid tank 2 is 85-110g / L, and the acid concentration of acid tank 3 is 115-145g / L. The temperature of the pickling is 85-95°C and the speed is 85-150m / min.
9. The preparation method according to claim 6, characterized in that: In step S3), the heating time = (sheet thickness × 125 + 60 ~ 100) s, the transfer time is 3 ~ 10 s, the heating atmosphere is dry compressed air, dry nitrogen or dry argon, and the dew point is -30 ~ -5 ° C; the hot stamping pressure is 1 ~ 20 MPa, the holding time is 3 ~ 15 s, and the quenching is to 80 ~ 180 ° C.
Citation Information
Patent Citations
Anti-oxidation ultrahigh-strength steel plate for hot stamping forming and low-temperature thermoforming process thereof
CN110643909A
Method for removing oxide skin of high Cr-Si alloying 1000-1800 MPa grade hot forming steel
CN114130842A
Hot forming steel with super-strong oxidation resistance and preparation method of hot forming steel
CN117265225A
Method for hot-forming a steel blank
CN108118242A